Desenvolvimento de uma cadeira de rodas robótica para transporte de portador de necessidades especiais - Oliveira Neto, Ivo Alves de (2013)
The objective of the dissertation was the realization of kinematic modeling of a robotic wheelchair using virtual chains, allowing the wheelchair modeling as a set of robotic manipulator arms forming a cooperative parallel kinematic chain. This document presents the development of a robotic wheelchair to transport people with special needs who overcomes obstacles like a street curb and barriers to accessibility in streets and avenues, including the study of assistive technology, parallel architecture, kinematics modeling, construction and assembly of the prototype robot with the completion of a checklist of problems and barriers to accessibility in several pathways, based on rules, ordinances and existing laws. As a result, simulations were performed on the chair in various states of operation to accomplish the task of going up and down stair with different measures, making the proportional control based on kinematics. To verify the simulated results we developed a prototype robotic wheelchair. This project was developed to provide a better quality of life for people with disabilities